A new autumn-flowering Crocus (Iridaceae) from Türkiye: C. rifatozdemiri sp. nov. - Şik, Levent; Yazici, Ceyda; Mollman, Rachel Rose; Harpke, Doerte; Kaleli, Bilge Saadet; Çiftçi, Almila; Erol, Osman (Phytotaxa, 2024)
C. rifatozdemiri sp. nov. is a new autumn-blooming species from Crocus series Crocus described from three locations on Mount Çal in Muğla province in southwest Türkiye. The new species is notable for its large showy white flowers with sharply mucronate segment tips and contrasting bright red stigma branches. The exceptionally tall stigma is what most clearly differentiates the new species from its closest relatives, with its long branches that usually divide from above the anther tips, although other morphological features, such as tunic neck and tepal shape, as well as molecular data, support its separation from other members of series Crocus. nrETS and nrITS nuclear regions were used to infer the phylogenetic affiliation of the new species within series Crocus, resulting in a clear separation between it and closest relative C. kofudagensis, as well as other members of the series. Leaf anatomy was found to be similar to other members of series Crocus, which tend to show minimal differences between species. Finally, a full description and diagnosis, chromosome count, line illustration and figures detailing the features of this new endemic taxon, which is so far known only from one mountain in Türkiye.